JAEPL, Vol. 16, Winter 2010-2011 - Joonna Smitherman Trapp (Editor); Brad Peters (Editor) (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
Essays Louann Reid - Imagination and Representation in Graphic Narratives Deborah F. Carrington & Chapman Hood Frazier - Transforming Tests: Finding the Poem Within Sara K. Schneider - Teaching to Students’ Kinesthetic Intelligence: The Teacher as Surrogate, Guru, Foreshadower, Choreographer, or Expeditionist Andrea Greenbaum - Nurturing Difference: The Autistic Student in Professional Writing Programs Ruth Henderson - The Forgiveness Classroom: Bringing Together Students from Both Sides of the Wall Julie Kearney - Writing as an Altered State of Consciousness: Process, Pedagogy, and Spirituality Anthony T. Atkins - It’s Complicated: Using Facebook to Create Emotional Connections in Student-Professor Relationships JoAnne Katzmarek - Weaving a Song of Self Out of the Box Bruce Novak - Taking the Great Leap of Being: Finding Happiness and Hope in a Life of Thought beyond the Academy Book Reviews Judy Halden-Sullivan - Practices in Mindfulness Ken DeLucca - Schoeberlein, Deborah and Suki Sheth. Mindful Teaching and Teaching Mindfulness: A Guide for Anyone Who Teaches Anything. Boston: Wisdom Publications, 2009. Brad Lucas - MacDonald, Elizabeth, and Dennis Shirley. The Mindful Teacher. New York: Teachers College Press, 2009. Timothy Shea - VanDeWeghe, Richard. Engaged Learning. Thousand Oaks, CA: Corwin, 2009. William Archibald - Cummings, Robert E. Lazy Virtues: Teaching Writing in the Age of Wikipedia. Nashville, TN: Vanderbilt UP, 2009 Connecting Helen Walker - Growing Up Grace Feuerverger - Mandy Gesa E. Kirsch - A Teaching Success or Failure? Betsy Newmeyer - My RIF’d Life Anita Voelker - Will’s Story Allison Brimmer - Elitist White Lady Who Tries Too Hard Debbie Axelrod - Dear Professor Walker Margo Wilson - Burnishing the Bruises Catherine M. Nelson - Jimmy Liang Zhao - Lead by Example